2020
DOI: 10.1177/0731684420960210
|View full text |Cite
|
Sign up to set email alerts
|

Physical and abrasive wear behaviour of Urena lobata fiber-reinforced polymer composites

Abstract: The influence of fiber loading and chemical treatment of Urena lobata natural fiber loading (5, 10, 15, 20, 25, 30, and 35 wt%) on the physical, wear, and thermal stability of polypropylene-based composites was investigated. Urena lobata fibers were treated with 6 wt% NaOH solution. Both the untreated and treated Urena lobata/polypropylene composites were produced by compression molding. The physical (density and water absorption) and abrasion properties of the composites were then evaluated. Thereafter, the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…In contrast, plowing is the extrusion of the polymer by abrasion to the sides, which does not directly cause material removal, but after several deformations can produce shedding and secondary chip formation. The rougher the counterpart surface, the greater the wear rate (WR) of the polymer (Dmitriyeva and Grayevskaya, 1983;Njoku et al, 2021). There may also be fatigue wear on the rough pair surface, when the friction pair slides against each other, the rough peaks of the soft surface are easily deformed, while the soft rough peaks break first under cyclic loading, resulting in a smoother surface.…”
Section: Friction and Wear Behavior And Improvement Mechanism Of The ...mentioning
confidence: 99%
“…In contrast, plowing is the extrusion of the polymer by abrasion to the sides, which does not directly cause material removal, but after several deformations can produce shedding and secondary chip formation. The rougher the counterpart surface, the greater the wear rate (WR) of the polymer (Dmitriyeva and Grayevskaya, 1983;Njoku et al, 2021). There may also be fatigue wear on the rough pair surface, when the friction pair slides against each other, the rough peaks of the soft surface are easily deformed, while the soft rough peaks break first under cyclic loading, resulting in a smoother surface.…”
Section: Friction and Wear Behavior And Improvement Mechanism Of The ...mentioning
confidence: 99%
“…Several research works showed that the additives added to the matrix phase lead to noticeable enhancement in properties which lead to opening a new room of applications for the same family of materials that could not achieve these requirements without the presence of additives as toughening agents or surface agents. [38][39][40][41][42] Additionally, further developments have shown that special improvements are noticed when using smaller reinforcing dimensions (so-called nano-composites), which cannot be reached with conventional fillers. The particle size and extent of surface area are generally proportional, either directly or indirectly to the performance of the polymeric matrix composites.…”
Section: Analysis Of Wear Performance Of Man-made Fibre-reinforced Po...mentioning
confidence: 99%
“…Few researchers utilized this Urena lobata fiber as a reinforcement in a polymer composite [ [36] , [37] , [38] , [39] ], sorbent materials [ 40 , 41 ], extraction of leaves used in pharmacology [ 35 ] as an anti-diabetic [ 42 ], antidiarrheal activity [ 43 , 44 ], antimicrobial activities [ 43 ] and antioxidant and cytotoxic activities [ 33 , 45 ]. Urena lobata fiber is also used in textile as fiber for blend yarn manufacturing [ 34 ].…”
Section: Introductionmentioning
confidence: 99%